Upaya Peningkatan Pengetahuan Remaja Tentang Anemia Gizi Besi di SMPN 1 Yosowilangun - Sabran, Sabran; Sari, Dian Kartika; Suandana, Iwan Abdi; Satya, Malinda Capri Nurul (SEJAGAT : Jurnal Pengabdian Masyarakat, 2025)
Iron Nutrition Anemia is a condition of blood hemoglobin deficiency that can reduce productivity and affect the cognitive development of adolescents. Adolescent girls are susceptible to anemia due to several causal factors. There is an increased need for iron during puberty. Another factor that causes anemia is low consumption of Fe and other nutrients such as vitamin A, vitamin C, folic acid, riboflavin, and B12.  This community service activity aims to increase adolescents' knowledge about AGB through educational programs at SMPN 1 Yosowilangun, Lumajang Regency. The activity was carried out in August 2024 and involved 30 teenagers in the 3rd grade of junior high school. The methods used included discourse and discussions supported by presentation media, leaflets, and the Freemia website. Through this activity, we hope to enhance teenagers' understanding of anemia risks, the significance of iron intake, and the importance of adopting a healthy diet to prevent anemia. Health education in schools is expected to be a strategic step in reducing the incidence of anemia in adolescents in Indonesia.